Synthesis and Optimization of 2,5-Dihydroxyterephthalic Acid in a Slurry Reactor - Reza Pirdadeh Beiranvand; Saeed Ovaysi (Journal of Chemistry)
2,5-Dihydroxyterephthalic acid (DHTA) is synthesized under 10 bar pressure and 200°C temperature. Using a slurry reactor, a disodium salt of hydroquinone (DSH) is contacted by carbon dioxide gas in the presence of sodium acetate as a catalyst. A fractional factorial design is used to screen four parameters including reactor pressure, temperature, catalyst-to-DSH molar ratio, and reaction time. By performing 8 experiments in the screening phase the variable ranges are modified to 175°C–200°C for temperature, 1.5–2.5 for catalyst-to-DSH molar ratio, and 3–5 h for reaction time. In addition, pressure is kept fixed at 10 bar throughout the remaining experiments. An additional 14 more experiments devised by the Box–Behnken design scheme are performed to determine a quadratic model for the DHTA yield against the three parameters mentioned above. A mathematical optimization of the model predicts 83.385% DHTA yield at 200°C, 2.085, and 250 min for temperature, catalyst-to-DSH molar ratio, and reaction time, respectively. These parameter values are put to the test by performing one more experiment under the suggested optimum point. This results in 83% DHTA yield which is in good agreement with the model. For all experiments, the DHTA yields and the composition of byproducts were obtained using HPLC analysis. The optimized product was analyzed using XRD and FTIR analyses and the structure of the synthesized DHTA was confirmed.